2020
DOI: 10.3390/biomedicines8070196
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Membrane Potential Predicts 4-Hour Sperm Motility

Abstract: The evaluation of conventional and biofunctional sperm parameters is of fundamental importance for assessing male reproductive function. Among these, sperm motility is one of the most important parameters. Indeed, asthenozoospermia is a frequent cause of male infertility. Sperm motility depends on mitochondrial function and the measurement of mitochondrial membrane potential (MMP) better accounts for the function of this intracellular organelle. On the basis of these premises, the present study assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Loss of MRP5 and MRP9 alters mitochondrial homeostasis, not only inducing vacuolated and aberrant mitochondria but also resulting in a significant reduction in sperm mitochondrial membrane potential as observed by JC-1 staining. This relationship between mitochondrial membrane potential and sperm function directly correlates with mitochondrial health, sperm motility, and modulation of respiratory chain activity and oxidative phosphorylation pathways ( 27 , 81 , 86 88 ). Concordantly, male fecundity relies heavily on this organelle and its membranes being fully intact and functional for the overall health of the spermatozoa and their fertilization capacity, cementing why DKO males show such significant loss of biological function ( 27 , 80 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MRP5 and MRP9 alters mitochondrial homeostasis, not only inducing vacuolated and aberrant mitochondria but also resulting in a significant reduction in sperm mitochondrial membrane potential as observed by JC-1 staining. This relationship between mitochondrial membrane potential and sperm function directly correlates with mitochondrial health, sperm motility, and modulation of respiratory chain activity and oxidative phosphorylation pathways ( 27 , 81 , 86 88 ). Concordantly, male fecundity relies heavily on this organelle and its membranes being fully intact and functional for the overall health of the spermatozoa and their fertilization capacity, cementing why DKO males show such significant loss of biological function ( 27 , 80 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a sperm agglutinating factor (SAF) was previously isolated from S. warneri and its recombinant version was recently proved as spermicidal in vitro, but also as an excellent contraception in vivo [ 27 ]. As mitochondrial membrane potential may predict 4-h sperm motility [ 28 ], intact mitochondria are an essential factor of sperm motion. Our research showed that semen samples infected mainly by S. aureus , S. warneri , S. cohnii , and S. kloosii were distinguished by the reduced mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of MRP5 and MRP9 alters mitochondrial homeostasis not only inducing vacuolated and aberrant mitochondria, but also resulting in a significant reduction in sperm mitochondrial membrane potential as observed by JC-1 staining. This relationship between mitochondrial membrane potential and sperm function directly correlates with mitochondrial health, sperm motility, and modulation of respiratory chain activity and oxidative phosphorylation pathways (27, 82, 8789). Concordantly, male fecundity relies heavily on this organelle and its membranes being fully intact and functional for the overall health of the spermatozoa and their fertilization capacity, cementing why DKO males show such significant loss of biological function (27, 8183).…”
Section: Discussionmentioning
confidence: 99%